PENERAPAN PENDEKATAN PEMBELAJARAN DISCOVERY LEARNING TERHADAP SELF CONFIDENCE SISWA SMP DI KABUPATEN PURWAKARTA - Lulu Marjani; Aris Rinaldi; Heris Hendriana; Ika wahyu Anita (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This research is aims to improve learning approach Discovery learning and Self Confidence to junior high school students on two linears equation. The research was conducted in one of Junior High School in Purwakarta. understanding of students in understanding the concept of system of linear equations of two variables is still very low because students emphasized the use of  formulas and routine exercises. because of that, the researcher seeks to apply learning approach Discovery Learning to stundents Self Confidence. this research uses classroom action research method which is implemented through two cycles consisting of one cycle on one meeting. the instrument used is the observation sheet, interview, preliminary tests and tests each cycle. In the preliminary tests showed that confidence in the mastery of the concept of linear equations of learners is still very low. On the cycle of a stundent's activities is listening explanation about the matter of concept of linear equation of two variable, identifiying, collecting information, and solving the problems that the teacher provides. On the one cycle many students are still confused in understanding the two-variable linear equation material and their confidence are still very low. In the second cycle the students has improved in understanding the concept of linear equations of two variables and has a good selfconfidence. The result of this research showed that the used of learning approach Discovery Learning on stundent's self confidence  on understanding the concept of linear equations of two variables has increased.